Covered tools and cutting tools

JP7936935B2Active Publication Date: 2026-10-16KYOCERA CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2025506613
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-14
Filing Date
2024-02-16
Publication Date
2026-10-16
Estimated Expiration
2044-02-16

Smart Images

  • Figure 0007936935000001
    Figure 0007936935000001
  • Figure 0007936935000002
    Figure 0007936935000002
  • Figure 0007936935000003
    Figure 0007936935000003
Patent Text Reader

Abstract

A coated tool according to one embodiment of the present disclosure comprises a substrate and a coating layer. The coating layer has a Mo-containing laminated structure in which the maximum value and the minimum value of the Mo content ratio in atomic percent alternately appear in the lamination direction. The Mo-containing laminated structure has a plurality of high-Mo-content layers and a plurality of low-Mo-content layers. The plurality of high-Mo-content layers include a plurality of first high-Mo-content layers and a plurality of second low-Mo-content layers which are positioned between the first high-Mo-content layers adjacent to each other in the lamination direction. When the maximum value of the first high-Mo-content layers is noted as first Mo maximum value, and the maximum value of the second high-Mo-content layers is noted as second Mo maximum value, the second Mo maximum value is smaller than the first Mo maximum value.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to coated tools and cutting tools. [Background technology]

[0002] Coated tools, which have improved wear resistance and other properties by coating the surface of a substrate such as cemented carbide, cermet, or ceramics with a coating layer, are known as cutting tools used in machining processes such as turning and milling. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2002-3284 [Overview of the project]

[0004] A coating tool according to one aspect of the present disclosure comprises a substrate and a coating layer located on the substrate, wherein the coating layer has a Mo-containing laminated structure in which a plurality of layers containing Mo are stacked, and in the stacking direction, maximum and minimum values ​​of the atomic percent Mo content ratio alternate, the Mo-containing laminated structure has a plurality of high Mo-content layers, each containing the maximum value, and a plurality of low Mo-content layers, each containing the minimum value, the plurality of high Mo-content layers has a plurality of first high Mo-content layers and a plurality of second high Mo-content layers, each located between adjacent first high Mo-content layers in the stacking direction, and when the maximum value of the first high Mo-content layer is taken as the first Mo maximum value and the maximum value of the second high Mo-content layer is taken as the second Mo maximum value, the second Mo maximum value is smaller than the first Mo maximum value. [Brief explanation of the drawing]

[0005] [Figure 1] Figure 1 is a perspective view showing an example of a coating tool according to an embodiment. [Figure 2] Figure 2 is a side cross-sectional view showing an example of a coating tool according to the embodiment. [Figure 3]Figure 3 is an enlarged cross-sectional view showing an example of a coating layer according to the embodiment. [Figure 4] Figure 4 is an enlarged cross-sectional view showing an example of a Ta-containing laminated structure and a Mo-containing laminated structure that constitute the coating layer according to the embodiment. [Figure 5] Figure 5 is an SEM image showing the distribution of Ta in a cross-section of a Ta-containing laminated structure according to an embodiment of this disclosure. [Figure 6] Figure 6 is a graph showing the distribution of Ta in a cross-section of a Ta-containing laminated structure according to an embodiment of the present disclosure. [Figure 7] Figure 7 is a graph showing the distribution of Ta and TI in a cross-section of a Ta-containing laminated structure according to an embodiment of the present disclosure. [Figure 8] Figure 8 is an SEM image showing the distribution of Mo in a cross-section of a Mo-containing laminated structure according to an embodiment of this disclosure. [Figure 9] Figure 9 is a graph showing the distribution of Mo in a cross-section of a Mo-containing laminated structure according to an embodiment of the present disclosure. [Figure 10] Figure 10 is a graph showing the distribution of Mo, Al, and Cr in a cross-section of a Mo-containing laminated structure according to an embodiment of the present disclosure. [Figure 11] Figure 11 is a schematic diagram showing an example of a film deposition apparatus for forming a coating layer on a substrate. [Figure 12] Figure 12 is a front view showing an example of a cutting tool according to an embodiment. [Figure 13] Figure 13 is a table showing the manufacturing conditions for the coating layer formed on the substrate. [Figure 14] Figure 14 is a table showing the results of cutting tests on coated tools for samples No. 1 to No. 12. [Modes for carrying out the invention]

[0006] The following describes in detail, with reference to the drawings, embodiments for implementing the coating tool 1 and cutting tool 100 according to this disclosure (hereinafter referred to as "embodiments"). Note that these embodiments do not limit the coating tool 1 and cutting tool 100 according to this disclosure. Furthermore, each embodiment can be combined as appropriate, provided that the processing content is not inconsistent. Also, the same parts are denoted by the same reference numerals in each of the following embodiments, and redundant descriptions are omitted.

[0007] Furthermore, in the embodiments described below, expressions such as "constant," "orthogonal," "perpendicular," or "parallel" may be used, but these expressions do not require that the lines be strictly "constant," "orthogonal," "perpendicular," or "parallel." In other words, each of the above expressions allows for deviations such as manufacturing accuracy or installation accuracy, with a deviation of approximately ±5% being permitted.

[0008] The conventional technologies described above have room for further improvement in terms of extending tool life. This disclosure has been made in view of the above and aims to provide coated tools and cutting tools that can extend tool life.

[0009] <Covered Tool 1> Figure 1 is a perspective view showing an example of a coating tool 1 according to the embodiment. Figure 2 is a side cross-sectional view showing an example of a coating tool 1 according to the embodiment. As shown in Figure 1, the coating tool 1 according to the embodiment has a tip body 2.

[0010] (Chip body 2) The chip body 2 has a hexahedron shape, for example, in which the top and bottom surfaces (the surfaces intersecting the Z-axis as shown in Figure 1) are parallelograms.

[0011] One corner of the chip body 2 functions as a cutting edge portion 3. The cutting edge portion 3 has a first surface (e.g., top surface) and a second surface (e.g., side surface) connected to the first surface. In the embodiment, the first surface functions as a "scooping surface" that scoops up chips generated by cutting, and the second surface functions as a "relief surface". Cutting edges are located on at least a portion of the ridge where the first surface and the second surface intersect, and the coated tool 1 cuts the workpiece by applying these cutting edges to the workpiece.

[0012] A through-hole 5 is located in the center of the chip body 2, passing through it vertically. A screw 75 for attaching the coating tool 1 to the holder 70, which will be described later, is inserted into the through-hole 5 (see Figure 12).

[0013] As shown in Figure 2, the chip body 2 has a substrate 10 and a coating layer 20.

[0014] (Base 10) The base body 10 is formed from, for example, a cemented carbide. The cemented carbide contains W (tungsten), specifically WC (tungsten carbide). The cemented carbide may also contain NI (nickel) and / or Co (cobalt). Specifically, the base body 10 is made of a WC-based cemented carbide in which WC particles are the hard phase component and Co is the main component of the binder phase.

[0015] Furthermore, the substrate 10 may be formed from a cermet. The cermet may contain, for example, TI (titanium), specifically TIC (titanium carbide) or TIN (titanium nitride). The cermet may also contain NI and / or Co.

[0016] Furthermore, the substrate 10 may be formed from a cubic boron nitride sintered body containing cubic boron nitride (cBN) particles. The substrate 10 is not limited to cubic boron nitride (cBN) particles, but may also contain particles such as hexagonal boron nitride (hBN), rhombohedral boron nitride (rBN), wurtzite boron nitride (wBN), etc.

[0017] Furthermore, the substrate 10 may be formed of ceramics. The ceramics may contain, for example, Al2O3 (aluminum oxide), such as κ-Al2O3 and α-Al2O3. The ceramics may also contain other elements in addition to aluminum oxide. For example, in addition to aluminum oxide, the ceramics may contain at least one of magnesium (Mg), calcium (Ca), strontium (Sr), silicon (SI), and a group 3 element of the periodic table.

[0018] (Coating layer 20) The coating layer 20 is applied to the substrate 10, for example, to improve the wear resistance, heat resistance, etc. of the substrate 10. The coating layer 20 may cover the entire substrate 10. The coating layer 20 only needs to be located on top of the substrate 10. When the coating layer 20 is located on the first surface (here, the top surface) of the substrate 10, the wear resistance and heat resistance of the first surface are high. When the coating layer 20 is located on the second surface (here, the side surface) of the substrate 10, the wear resistance and heat resistance of the second surface are high.

[0019] Furthermore, an intermediate layer 21 may be located between the substrate 10 and the coating layer 20. Specifically, the intermediate layer 21 is in contact with the upper surface of the substrate 10 on one side (in this case, the lower surface) and in contact with the lower surface of the coating layer 20 (for example, the Ta-containing laminated structure 22) on the other side (in this case, the upper surface).

[0020] Here, the specific configuration of the coating layer 20 will be described with reference to Figures 3, 4, 5, and 6. Figure 3 is an enlarged cross-sectional view showing an example of the coating layer 20 according to the embodiment. Figure 4 is an enlarged cross-sectional view showing an example of the Ta-containing laminated structure 22 and Mo-containing laminated structure 23 that constitute the coating layer 20 according to the embodiment.

[0021] As shown in Figure 3, the coating layer 20 may include a plurality of Ta-containing laminated structures 22 and a plurality of Mo-containing laminated structures 23 located on the intermediate layer 21. Each of the plurality of Ta-containing laminated structures 22 is a laminated structure containing at least Ta. Each of the plurality of Mo-containing laminated structures 23 is a laminated structure containing at least Mo.

[0022] As shown in Figure 3, the multiple Ta-containing laminated structures 22 and the multiple Mo-containing laminated structures 23 may be alternately laminated within the coating layer 20. The Z direction shown in Figure 3 may also be referred to as the lamination direction.

[0023] In such cases, residual stress between the Ta-containing laminated structure 22 and the Mo-containing laminated structure 23 can be reduced. This reduces delamination or cracking between the Ta-containing laminated structure 22 and the Mo-containing laminated structure 23. Furthermore, the effects of the Ta-containing laminated structure 22 and the Mo-containing laminated structure 23, as described later, can be improved. As a result, the lifespan of the coated tool 1 can be extended.

[0024] The average thickness of each of the multiple Ta-containing laminated structures 22 and the multiple Mo-containing laminated structures 23 may be between 300 nm and 500 nm.

[0025] In such cases, residual stress between the Ta-containing laminated structure 22 and the Mo-containing laminated structure 23 can be reduced. This reduces delamination or cracking between the Ta-containing laminated structure 22 and the Mo-containing laminated structure 23. Furthermore, the effects of the Ta-containing laminated structure 22 and the Mo-containing laminated structure 23, as described later, can be improved. As a result, the lifespan of the coated tool 1 can be extended.

[0026] (Middle class 21) The intermediate layer 21 has higher adhesion to the substrate 10 compared to the coating layer 20. Examples of metal elements having such properties include Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, SI, Y, and TI. The intermediate layer 21 contains at least one of the above metal elements. For example, the intermediate layer 21 may contain TI. Although SI is a metalloid element, in this specification, metalloid elements are also included in the definition of metal elements.

[0027] If the intermediate layer 21 contains TI, the TI content in the intermediate layer 21 may be 1.5 atomic percent or more. For example, the TI content in the intermediate layer 21 may be 2 atomic percent or more.

[0028] The intermediate layer 21 may contain components other than the above-mentioned metal elements (Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, SI, Y, TI). However, from the viewpoint of adhesion to the substrate 10, the intermediate layer 21 may contain at least 95 atomic percent of the above-mentioned metal elements in total. More preferably, the intermediate layer 21 may contain 98 atomic percent or more of the above-mentioned metal elements in total. The proportion of metal components in the intermediate layer 21 can be determined, for example, by analysis using an EDS (energy-dispersive X-ray spectrometer) attached to a STEM (scanning transmission electron microscope).

[0029] In this way, by providing an intermediate layer 21 between the substrate 10 and the coating layer 20, which has a higher wettability with the substrate 10 compared to the coating layer 20, the adhesion between the substrate 10 and the coating layer 20 can be improved. Furthermore, since the intermediate layer 21 also has high adhesion with the coating layer 20, it is unlikely that the coating layer 20 will peel off from the intermediate layer 21. The thickness of the intermediate layer 21 may be, for example, 0.1 nm or more and less than 20 nm.

[0030] (Ta-containing laminated structure 22) The Ta-containing laminated structure 22 may consist of multiple layers containing Ta, and the maximum and minimum values ​​of the atomic percent Ta content ratio may alternate in the stacking direction.

[0031] Here, the specific configuration of the Ta-containing laminated structure 22 will be described with reference to Figures 5, 6, and 7. Figure 5 is an SEM image showing the distribution of Ta in a cross-section of the Ta-containing laminated structure 22 according to an embodiment of this disclosure. Figure 6 is a graph showing the distribution of Ta in a cross-section of the Ta-containing laminated structure 22 according to an embodiment of this disclosure.

[0032] The "distance (nm)" on the horizontal axis of the graph shown in Figure 6 corresponds to the distance of bar T1 extending in the Z direction (stacking direction) as shown in Figure 5. Bar T1 may be located at the center of the Ta-containing laminated structure 22 in the Z direction (stacking direction) as shown in Figure 5. The black dots in the graph shown in Figure 6 represent the first Ta maximum, second Ta maximum, first Ta minimum, and second Ta minimum values, which will be described later. Figure 7 is a graph showing the distribution of Ta and TI in a cross-section of the Ta-containing laminated structure 22 according to an embodiment of this disclosure. The "distance (nm)" on the horizontal axis of the graph shown in Figure 7 is the same as the "distance (nm)" on the horizontal axis of the graph shown in Figure 6.

[0033] Furthermore, the Ta-containing laminated structure 22 includes a plurality of high-Ta content layers 22a and a plurality of low-Ta content layers 22b. The high-Ta content layers 22a may contain Ta in a higher proportion than the low-Ta content layers 22b. Each high-Ta content layer 22a may have a maximum value of the atomic percentage of Ta in the stacking direction. Each low-Ta content layer 22b may have a minimum value of the atomic percentage of Ta in the stacking direction.

[0034] The multiple Ta-high-content layers 22a may consist of multiple first Ta-high-content layers 22aa, or a second Ta-high-content layer 22ab located between adjacent first Ta-high-content layers 22aa in the stacking direction. The multiple Ta-high-content layers 22a may consist of multiple second Ta-high-content layers 22ab. Here, when the maximum value of the first Ta-high-content layer 22aa is defined as the first Ta maximum value, and the maximum value of the second Ta-high-content layer 22ab is defined as the second Ta maximum value, the second Ta maximum value may be smaller than the first Ta maximum value.

[0035] When the coating layer 20 has a simple nanolayer structure, the compressive residual stress inside the coating layer 20 becomes high, increasing the risk of chipping and other delamination issues. However, when the second Ta maximum value is smaller than the first Ta maximum value, the compressive residual stress inside the coating layer 20 is more easily reduced, and the hardness of the coating layer 20 tends to increase. Furthermore, the risk of oxidation progressing inside the coating layer 20 during machining can be reduced.

[0036] Furthermore, as shown in Figure 6, the first Ta-high-content layer 22aa may have only one maximum value and may not have any other maximum or minimum values. Similarly, as shown in Figure 6, the second Ta-high-content layer 22ab may also have only one maximum value and may not have any other maximum or minimum values.

[0037] Here, the proportion of metal components in the Ta-containing laminated structure 22 can be determined, for example, by analysis using EDS attached to the STEM. Figure 6 shows the quantitative distribution obtained by analysis using EDS, and is a graph created based on data of the atomic percentage of Ta content in the Ta-containing laminated structure 22 averaged over 15 points. By creating a graph under these conditions, it is possible to observe the maximum and minimum values ​​in the embodiment of this disclosure while excluding very small peaks that do not affect the performance of the coating layer 20.

[0038] The multiple Ta-low content layers 22b may have multiple first Ta-low content layers 22ba, or they may have second Ta-low content layers 22bb located between adjacent first Ta-low / high content layers in the stacking direction. The multiple Ta-low content layers 22b may have multiple second Ta-low content layers 22bb. Here, when the minimum value of the first Ta-low content layer 22ba is called the first Ta minimum, and the minimum value of the second Ta-low content layer 22bb is called the second Ta minimum, the second Ta minimum may be greater than the first Ta minimum.

[0039] Furthermore, as shown in Figure 6, the first low-Ta content layer 22ba may have only one local minimum and may not have any other local minimums or maximums. Similarly, as shown in Figure 6, the second low-Ta content layer 22bb may also have only one local minimum and may not have any other local minimums or maximums.

[0040] Furthermore, as shown in Figure 6, the Ta-containing laminated structure 22 may have multiple layers arranged in the stacking direction in the order of a first high-Ta content layer 22aa, a second low-Ta content layer 22bb, a second high-Ta content layer 22ab, and a first low-Ta content layer 22ba. In these four arranged layers, the ratio of the difference between the second maximum Ta value and the second minimum Ta value to the difference between the first maximum Ta value and the first minimum Ta value may be 20% or more, or 80% or less.

[0041] Furthermore, in the Ta-containing laminated structure 22, when multiple layers arranged in the stacking direction in the order of a first high-Ta content layer 22aa, a second low-Ta content layer 22bb, a second high-Ta content layer 22ab, a first low-Ta content layer 22ba, a second high-Ta content layer 22ab, and a second low-Ta content layer 22bb are considered as one Ta-containing layer, the Ta-containing layers may be arranged repeatedly. Here, "arranged repeatedly" means that at least three or more Ta-containing layers are arranged. Here again, in the multiple arranged layers, the ratio of the difference between the second maximum Ta value and the second minimum Ta value to the difference between the first maximum Ta value and the first minimum Ta value may be 20% or more, or 80% or less.

[0042] The first Ta maximum value may be greater than the atomic percentage of Ta in the entire Ta-containing laminated structure 22. In such cases, the risk of oxidation progressing inside the coating during machining can be reduced. Here, the atomic percentage of Ta in the entire Ta-containing laminated structure 22 may be the average value of the atomic percentage of Ta contained in the coating layer 20. In Figure 6, the average value of the atomic percentage of Ta contained in the 65 mm region in the lamination direction of the Ta-containing laminated structure 22 is shown by the dashed line L1, and the first Ta maximum value is greater than the value of L1.

[0043] The second Ta maximum value may be smaller than the atomic percentage of Ta in the entire Ta-containing laminated structure 22. In such cases, the hardness of the coating layer 20 tends to be even higher. In Figure 6, the second Ta maximum value is smaller than the value of L1. The second Ta maximum value may be smaller than the atomic percentage of Ta in the entire Ta-containing laminated structure 22.

[0044] The first Ta minimum may be smaller than the atomic percentage of Ta in the entire Ta-containing laminated structure 22. In Figure 6, the first Ta minimum is smaller than the value of L1. The second Ta minimum may be larger than the atomic percentage of Ta in the entire Ta-containing laminated structure 22. In Figure 6, the second Ta maximum is larger than the value of L1. The second Ta minimum may be smaller than the atomic percentage of Ta in the entire Ta-containing laminated structure 22.

[0045] Multiple second Ta-high-content layers 22ab may be located between adjacent first Ta-high-content layers 22aa in the lamination direction. In such cases, residual stress is easier to reduce, the crack dispersion effect is enhanced, and the coating is more likely to become tougher. The Ta-containing laminated structure 22 may have multiple layers arranged in the lamination direction in the following order: first Ta-high-content layer 22aa, second Ta-low-content layer 22bb, second Ta-high-content layer 22ab, first Ta-low-content layer 22ba, second Ta-high-content layer 22ab, second Ta-low-content layer 22bb, and first Ta-high-content layer 22aa.

[0046] Furthermore, the first high-Ta layer 22aa may mean a layer exhibiting a Ta content of 150% or more of the average value of the Ta content ratio in atomic percent. The first low-Ta layer 22ba may mean a layer exhibiting a Ta content of 70% or less of the average value of the Ta content ratio in atomic percent. The second high-Ta layer 22ab and the second Ta low Containing layer 22 bb This may mean a layer exhibiting a Ta content ratio of 70-150% of the average value of the Ta content ratio in atomic percent.

[0047] The Ta-containing laminated structure 22 may contain a light metal. Here, the light metal may be a metal element having a specific gravity of 4 or less. More specifically, it may be Al and / or Ti. In such a case, the coating layer 20 having excellent oxidation resistance, wear resistance, and lubricity can be easily obtained.

[0048] In the Ta distribution in the cross section of the Ta-containing laminated structure 22, the content ratio of composition X is defined as I X , I X the maximum value is I X_max , I X the minimum value is I X_mIn , I X the average value is I X_ave , I X the range is I X_ave the value divided by is defined as δI X (=(I X_max -I X_mIn ) / I X_ave ), it may satisfy δI A <δI Ta .

[0049] In such a case, the risk of oxidation progressing inside the coating during cutting can be reduced. In addition, the risk of local lattice distortion caused by the addition of Ta is easily reduced, and the risk of film peeling in the coating is easily reduced. In the coating layer 20 according to the present disclosure, 0.1≦δI A ≦0.6 and 1.0≦δI Ta ≦2.5. In addition, in the present disclosure, the element distribution is calculated from the content ratio of each metal element in atomic % in a region of 65 nm in the lamination direction in the Ta-containing laminated structure 22.

[0050] The Ta-containing laminated structure 22 may have a first Ta region 22A, and a second Ta region 22B located farther from the base body 10 than the first Ta region 22A. Further, the content ratio of the composition X in the first Ta region 22A is defined as I X1 , I X1 the range is I X_ave the value divided by is defined as δI X1 , the content ratio of the composition X in the second Ta region 22B is defined as I X2 , IX2 The range of I X_ave The value obtained by dividing by δI X2 In that case, δI Ta2 <δI Ta1 This is also possible. In such cases, residual stress between the substrate 10 and the coating layer 20 can be easily reduced, and the risk of delamination between the coating layers 20 can be further reduced.

[0051] (Mo-containing laminated structure 23) The Mo-containing laminated structure 23 may consist of multiple layers containing Mo, and the maximum and minimum values ​​of the atomic percent Mo content ratio may alternate in the stacking direction.

[0052] Here, the specific configuration of the Mo-containing laminated structure 23 will be described with reference to Figures 8, 9, and 10. Figure 8 is an SEM image showing the distribution of Mo in a cross-section of the Mo-containing laminated structure 23 according to an embodiment of this disclosure. Figure 9 is a graph showing the distribution of Mo in a cross-section of the Mo-containing laminated structure 23 according to an embodiment of this disclosure.

[0053] The "distance (nm)" on the horizontal axis of the graph shown in Figure 9 corresponds to the distance of bar T2 extending in the Z direction (stacking direction) as shown in Figure 8. Bar T2 may be located at the center of the Mo-containing laminated structure 23 in the Z direction (stacking direction) as shown in Figure 8. The black dots in the graph shown in Figure 9 indicate the first Mo maximum, second Mo maximum, first Mo minimum, and second minimum values, which will be described later. Figure 10 is a graph showing the distribution of Mo, Al, and Cr in a cross-section of the Mo-containing laminated structure 23 according to an embodiment of this disclosure. The "distance (nm)" on the horizontal axis of the graph shown in Figure 10 is the same as the "distance (nm)" on the horizontal axis of the graph shown in Figure 9.

[0054] Furthermore, the Mo-containing laminated structure 23 includes a plurality of high-Mo-content layers 23a and a plurality of low-Mo-content layers 23b. The high-Mo-content layers 23a may contain Mo in a higher proportion than the low-Mo-content layers 23b. Each high-Mo-content layer 23a may have a maximum value of the atomic percent Mo content ratio in the stacking direction. Each low-Mo-content layer 23b may have a minimum value of the atomic percent Mo content ratio in the stacking direction.

[0055] The multiple Mo-high-content layers 23a may consist of multiple first Mo-high-content layers 23aa, or a second Mo-high-content layer 23ab located between adjacent first Mo-high-content layers 23aa in the stacking direction. The multiple Mo-high-content layers 23a may consist of multiple second Mo-high-content layers 23ab. Here, when the maximum value of the first Mo-high-content layer 23aa is defined as the first Mo maximum value, and the maximum value of the second Mo-high-content layer 23ab is defined as the second Mo maximum value, the second Mo maximum value may be smaller than the first Mo maximum value.

[0056] If the coating layer 20 has a simple nanolayer structure, the compressive residual stress inside the coating layer 20 will increase, which increases the risk of peeling such as chipping. However, if the second Mo maximum value is smaller than the first Mo maximum value, the second Mo high-content layer 23ab will become harder, and the effect of the decrease in the overall hardness of the coating layer 20 due to Mo addition can be kept to a minimum.

[0057] Furthermore, as shown in Figure 9, the first Mo-high content layer 23aa may have only one maximum value and may not have any other maximum or minimum values. Similarly, as shown in Figure 9, the second Mo-high content layer 23ab may also have only one maximum value and may not have any other maximum or minimum values.

[0058] Here, the proportion of metal components in the Mo-containing laminated structure 23 can be determined, for example, by analysis using EDS attached to the STEM. Figure 9 shows the quantitative distribution obtained by analysis using EDS, and is a graph created based on data of the atomic percentage Mo content ratio in the Mo-containing laminated structure 23 averaged over 15 points. By creating a graph under these conditions, it is possible to observe the maximum and minimum values ​​in this disclosure while excluding very small peaks that do not affect the performance of the coating layer 20.

[0059] The multiple low Mo content layers 23b may have multiple first low Mo content layers 23ba, or they may have second low Mo content layers 23bb located between adjacent first low-to-high Mo content layers in the stacking direction. The multiple low Mo content layers 23b may have multiple second low Mo content layers 23bb. Here, when the minimum value of the first low Mo content layer 23ba is called the first Mo minimum, and the minimum value of the second low Mo content layer 23bb is called the second Mo minimum, the second Mo minimum may be greater than the first Mo minimum.

[0060] Furthermore, as shown in Figure 9, the first low-Mo content layer 23ba may have only one local minimum and may not have any other local minimums or maximums. Similarly, as shown in Figure 9, the second low-Mo content layer 23bb may also have only one local minimum and may not have any other local minimums or maximums.

[0061] Furthermore, as shown in Figure 9, the Mo-containing laminated structure 23 may have multiple layers arranged in the stacking direction in the order of a first high-Mo-content layer 23aa, a second low-Mo-content layer 23bb, a second high-Mo-content layer 23ab, and a first low-Mo-content layer 23ba. In these four arranged layers, the ratio of the difference between the second maximum Mo value and the second minimum Mo value to the difference between the first maximum Mo value and the first minimum Mo value may be 20% or more, or 80% or less.

[0062] Furthermore, in the Mo-containing laminated structure 23, when multiple layers arranged in the stacking direction in the order of a first high-Mo-content layer 23aa, a second low-Mo-content layer 23bb, a second high-Mo-content layer 23ab, a first low-Mo-content layer 23ba, a second high-Mo-content layer 23ab, and a second low-Mo-content layer 23bb are considered as one Mo-containing layer, the Mo-containing layers may be arranged in a repeating pattern. Here, "arranged in a repeating pattern" means that at least three or more Mo-containing layers are arranged in a repeating pattern. Here again, in the multiple layers arranged in a repeating pattern, the ratio of the difference between the second maximum-Mo value and the second minimum-Mo value to the difference between the first maximum-Mo value and the first minimum-Mo value may be 20% or more, or 80% or less.

[0063] The first Mo maximum value may be greater than the atomic percentage of Mo content in the entire Mo-containing laminated structure 23. In such cases, effects such as improved lubricity, high-temperature stability (suppression of softening and compositional deformation), and improved oxidation resistance are more likely to occur. Here, the atomic percentage of Mo content in the entire Mo-containing laminated structure 23 may be the average value of the atomic percentage of Mo content in the coating layer 20. In Figure 9, the average value of the atomic percentage of Mo content contained in the region 65 nm in the stacking direction within the Mo-containing laminated structure 23 is shown by the dashed line L2, and the first Mo maximum value is greater than the value of L2.

[0064] The second Mo maximum value may be smaller than the atomic percentage of Mo content in the entire Mo-containing laminated structure 23. In such cases, the risk of hardness reduction due to Mo addition can be further reduced, and the risk of internal fracture of the coating layer 20 can also be further reduced. In Figure 9, the second Mo maximum value is smaller than the value of L2. The second Mo maximum value may be smaller than the atomic percentage of Mo content in the entire Mo-containing laminated structure 23.

[0065] The first Mo minimum may be smaller than the atomic percentage of Mo in the entire Mo-containing laminated structure 23. In Figure 9, the first Mo minimum is smaller than the value of L2. The second Mo minimum may be larger than the atomic percentage of Mo in the entire Mo-containing laminated structure 23. In Figure 9, the second Mo minimum is larger than the value of L2. The second Mo minimum may be smaller than the atomic percentage of Mo in the entire Mo-containing laminated structure 23.

[0066] Multiple second Mo-high-content layers 23ab may be located between adjacent first Mo-high-content layers 23aa in the stacking direction. In such cases, the risk of internal failure of the coating layer 20 can be further reduced. The Mo-containing laminated structure 23 may have multiple layers arranged in the stacking direction in the order of first Mo-high-content layer 23aa, second Mo-low-content layer 23bb, second Mo-high-content layer 23ab, first Mo-low-content layer 23ba, second Mo-low-content layer 23bb, second Mo-high-content layer 23ab, and first Mo-high-content layer 23aa.

[0067] Furthermore, the first Mo-high-content layer 23aa may mean a layer exhibiting a Mo content of 120% or more of the average value of the Mo content ratio in atomic percent. The first Mo-low-content layer 23ba may mean a layer exhibiting a Mo content of 75% or less of the average value of the Mo content ratio in atomic percent. The second Mo-high-content layer 23ab and the second Mo low Contained layer 23 bb This may mean a layer exhibiting a Mo content ratio of 75-120% of the average value of the Mo content ratio in atomic percent.

[0068] The Mo-containing laminated structure 23 may also contain light metals. Here, light metals may be metallic elements with a specific gravity of 4 or less. More specifically, they may be Al and / or Cr.

[0069] In the elemental distribution in the cross-section of the Mo-containing laminated structure 23, the content ratio of composition Y is I Y , I Y I Y_max , I Y The minimum value of I Y_mIn , IY The average value of I Y_ave , I Y The range of I Y_ave The value obtained by dividing by δI Y (=(I Y_max -I Y_mIn ) / I Y_ave In the case of ) δI A <δI Mo That's fine.

[0070] In such cases, the effects of Mo, such as chipping resistance, fracture resistance, lubricity, and heat resistance, are more easily achieved while maintaining the oxidation resistance that is the effect of Al addition. In the coating layer 20 of this disclosure, 0.2 ≤ δI A ≤1.0, 0.7 ≤δI Mo The value is ≤2.5. In this disclosure, the elemental distribution is calculated from the atomic percentage content ratio of each metal element contained in a region of 65 nm in the layer thickness direction within the Mo-containing laminated structure 23.

[0071] δI Cr <δI Mo This is also acceptable. In such cases, the wear resistance, which is the effect of Cr addition, is maintained while the effects of Mo, such as chipping resistance, fracture resistance, lubricity, and heat resistance, are more easily achieved.

[0072] The Mo-containing laminated structure 23 may have a first Mo region 23A and a second Mo region 23B located further from the substrate 10 than the first Mo region 23A. Furthermore, the content ratio of composition Y in the first Mo region 23A may be I Y1 , I Y1 The range of I Y1 The average value (I Y1_ave The value obtained by dividing by ) is δI Y1 (=(I Y1_max -I Y1_mIn ) / I Y1_ave ), the content ratio of composition Y in the second Mo region 23B is I Y2 , I Y2 The range of I Y2 The average value (I Y2_ave The value obtained by dividing by ) is δI Y2 (=(I Y2_max -I Y2_mIn) / I Y2_ave When ) is set, δI Mo2 <δI Mo1 This is also possible. In such cases, residual stress between the substrate 10 and the coating layer 20 can be easily reduced, and the risk of delamination between the coating layers 20 can be further reduced.

[0073] The average thickness of the high-Ta layer 22a, low-Ta layer 22b, high-Mo layer 23a, and low-Mo layer 23b is preferably 3 nm or more and 15 nm or less.

[0074] In this case, the Ta-containing laminated structure 22, which includes a high-Ta layer 22a and a low-Ta layer 22b, is a laminated structure of multiple layers having a nanoscale thickness. Similarly, the Mo-containing laminated structure 23, which includes a high-Mo layer 23a and a low-Mo layer 23b, is a laminated structure of multiple layers having a nanoscale thickness. This improves the strength of the coating layer 20 against external forces. It also improves the oxidation resistance and high-temperature hardness of the coating layer 20. As a result, the lifespan of the coated tool 1 can be extended.

[0075] <Manufacturing method for the covering tool 1> Next, an example of a method for manufacturing the coated tool 1 according to the embodiment will be described with reference to Figure 11. Figure 11 is a schematic diagram showing an example of a film deposition apparatus for forming a coating layer 20 on a substrate 10. Note that the method for manufacturing the coated tool 1 is not limited to the method shown below.

[0076] First, a substrate 10 having the shape of a coating tool 1 is fabricated using a conventionally known method. Next, a coating layer 20 is formed on the surface of the substrate 10. As a method for forming the coating layer 20, for example, a physical vapor deposition (PVD) method such as ion plating or sputtering can be used. For example, when fabricating the coating layer 20 by ion plating, an arc ion plating apparatus (hereinafter referred to as AIP apparatus) 1000 as shown in Figure 11 can be used.

[0077] The AIP apparatus 1000 shown in Figure 11 introduces a gas such as N2 or Ar into a vacuum chamber 101 through a gas inlet 102, and applies a high voltage between the cathode electrode 103 and anode electrode 104 located in the AIP apparatus 1000 to generate a gas plasma. This plasma evaporates and ionizes the desired metal or ceramic from the target 105, generating high-energy ions of the metal or ceramic. These ionized metal or ceramic is then deposited onto the surface of the substrate 10, which serves as the sample, to form a coating layer 20 on the surface of the substrate 10.

[0078] Furthermore, as shown in Figure 11, multiple base units 10 may be set on the tower 107 and placed on the sample support stand 106. Alternatively, multiple (two sets in the figure) sample support stands 106 may be placed on a table not shown. In addition, as shown in Figure 11, a heater 108 for heating the base unit 10, a gas outlet 109 for discharging gas to the outside of the system, and a bias power supply 110 for applying a bias voltage to the base unit 10 are provided.

[0079] For example, the target 105 can be a metal target containing independently metallic tantalum (Ta), metallic molybdenum (Mo), and one or more metals selected from Group 5 or Group 6 elements of the periodic table, SI, Y, and Ce; an alloy target formed by combining these; or a mixed target consisting of powders or sintered bodies of carbides, nitrides, or borides thereof.

[0080] Then, using target 105, the metal source is evaporated by arc discharge or glow discharge, ionizing the metal in the metal source. At the same time, by reacting it with nitrogen (N2) gas from the nitrogen source, methane (CH4) / acetylene (C2H2) gas from the carbon source, or oxygen (O2) gas, a coating layer 20 is deposited on the surface of substrate 10.

[0081] At that time, the sample support stand 106 is controlled so that the distance from the position of the target 105 to the position of the base 10 is 160 mm or more, preferably 260 mm or more. In addition, a large number of highly directional magnetic field lines are generated from the center of the surface of the target 105 toward the base 10, so that the magnetic flux density near the base 10 is 0.2 to 0.8 mT (millitesla).

[0082] Preferably, nitrogen gas is introduced as a reaction gas into the AIP apparatus 1000 to create an atmospheric pressure of 2 to 10 Pa. The temperature of the substrate 10 is maintained at 300 to 500°C. Furthermore, a bias voltage of -50 to -200 V is applied to the substrate 10 to generate an arc discharge of 80 to 200 A between the target 105 (cathode electrode 103) and the anode electrode 104. Then, metal is deposited onto the substrate 10 while it is rotating on its own axis and on its orbit.

[0083] As a method for controlling the magnetic flux density near the base 10, for example, the magnetic field can be controlled by installing an electromagnetic coil or permanent magnet, which is a magnetic field source, around the target 105, by placing a permanent magnet inside the AIP device 1000, for example, in the center, or by adjusting the position of adjacent targets 105.

[0084] The magnetic force is calculated by measuring the magnetic flux density at the base body 10 using a magnetic flux densimeter. The magnetic flux density is expressed in units of mT (millitesla). Here, the distance from the position of the target 105 to the position of the base body 10 represents the distance measured at the position where the base body 10 is closest to the target 105, and the distance at which the base body 10 is furthest from the target 105.

[0085] Furthermore, during film formation, the period at which the substrate 10 is closest to the target 105 at each position of the substrate 10 as shown in Figure 11 is defined as the rotation speed of the sample. By adjusting the rotation speed, the period of the difference in composition between heavy metals and light metals in the thickness direction of the coating layer 20 can be adjusted. Specifically, it is desirable to adjust the rotation speed of the substrate 10 and the sample support stand 106 so that the period is 2 to 20 rpm (revolutions per minute).

[0086] Furthermore, during film deposition, the tower 107 may rotate while each of the sample support stages 106 on which the substrate 10 is placed rotates, and the table may be rotated so that multiple sample support stages 106 revolve. By adjusting the timing of these revolves, the thickness of each compound layer constituting the Ta-containing laminated structure 22 and the Mo-containing laminated structure 23 can be controlled.

[0087] Furthermore, by applying a pulsed bias voltage, the time or distance over which metal ions travel from the target 105 to the substrate 10 can be adjusted. This makes it possible to create differences in the composition of heavy metal components and light metal components during film formation.

[0088] More specifically, by applying a steady-state bias voltage of -50 to -200V while simultaneously applying a pulsed bias voltage of -100 to -200V with a period of 1 to 5 seconds and a pulse width of 300 to 700 nsec, it is possible to generate a second Ta maximum value smaller than the first Ta maximum value, and also a second Mo maximum value smaller than the first Mo maximum value.

[0089] By increasing the pulsed bias voltage described above, the first Ta maximum value can be made larger than the atomic percentage of Ta content in the entire Ta-containing laminated structure 22, and the first Mo maximum value can be made larger than the atomic percentage of Mo content in the entire Mo-containing laminated structure 23.

[0090] By lowering the pulsed bias voltage described above, the second Ta maximum value can be made smaller than the atomic percentage of Ta content in the entire Ta-containing laminated structure 22, and the second Mo maximum value can be made smaller than the atomic percentage of Mo content in the entire Mo-containing laminated structure 23.

[0091] By shortening the period of the pulsed bias voltage and adjusting the pulse width between 300 and 700 nsec, multiple second Ta-high-content layers 22ab can be positioned between adjacent first Ta-high-content layers 22aa in the stacking direction, and multiple second Mo-high-content layers 23ab can be positioned between adjacent first Mo-high-content layers 23aa in the stacking direction.

[0092] By repeating these processes, a configuration can be achieved in which the plurality of first Ta-high-content layers 22aa and the plurality of second Ta-high-content layers 22ab are alternately located in the stacking direction, and a configuration can be achieved in which the plurality of first Mo-high-content layers 23aa and the plurality of second Mo-high-content layers 23ab are alternately located in the stacking direction.

[0093] By setting the arc current flowing through the Ta-containing target to 100A or more, and the rotation speed (rotational speed) of the tower to 5 rpm or less, δI A <δI Ta It can be done this way.

[0094] By setting the arc current flowing through the Mo-containing target to 100A or more, and the rotation speed (rotational speed) of the tower to 5 rpm or less, δI Cr <δI Mo It can be done this way.

[0095] By making the arc current flowing through the target during the formation of the second Ta region 22B smaller than the arc current during the formation of the first Ta region 22A, and by making the rotation speed (rotational speed) of the tower higher than the speed during the formation of the first Ta region 22A, δI Ta2 <δI Ta1 This can be achieved. Furthermore, by making the arc current flowing through the target during the formation of the second Mo region 23B smaller than the arc current during the formation of the first Mo region 23A, and by making the rotation speed (rotational speed) of the tower higher than the speed during the formation of the first Mo region 23A, δI Mo2 <δI Mo1 It can be done this way.

[0096] For example, if the substrate 10 is positioned so that it approaches and faces the target 105, heavy metal components from the target 105 will fly in a straight line to the substrate 10, resulting in more heavy metals accumulating on the substrate 10 than light metals. On the other hand, if the substrate 10 is positioned so that it is far from the target 105 and does not face it, light metal components will wrap around and accumulate on the substrate 10, so the amount of heavy metal components deposited is expected to decrease. In this case, by increasing the distance from the position of the target 105 to the position of the substrate 10 and maintaining a certain magnetic flux density near the substrate 10, the wrapping of light metal components is promoted, and the compositional difference between heavy metal components and light metal components is expected to increase.

[0097] <Cutting tools 100> Next, the configuration of the cutting tool 100 equipped with the coating tool 1 described above will be explained with reference to Figure 12. Figure 12 is a front view showing an example of the cutting tool 100 according to the embodiment.

[0098] As shown in Figure 12, the cutting tool 100 according to this embodiment comprises a coating tool 1 and a holder 70 for fixing the coating tool 1.

[0099] The holder 70 is a rod-shaped member extending from the first end (upper end in Figure 12) to the second end (lower end in Figure 12). The holder 70 is made of, for example, steel or cast iron. In particular, it is preferable to use steel, which has high toughness among these materials.

[0100] The holder 70 has a pocket 73 at the end on the first end side. The pocket 73 is the part into which the coated tool 1 is mounted, and has a seating surface that intersects with the rotational direction of the workpiece, and a restraining side surface that is inclined with respect to the seating surface. The seating surface is provided with a screw hole 75 into which a screw 75, which will be described later, is screwed.

[0101] The coating tool 1 is located in the pocket 73 of the holder 70 and is attached to the holder 70 by a screw 75. Specifically, the screw 75 is inserted into the through hole 5 of the coating tool 1, and the tip of the screw 75 is inserted into the screw hole 75 formed in the seating surface of the pocket 73, thereby screwing the two screw portions 75 together. In this way, the coating tool 1 is attached to the holder 70 such that the cutting edge portion 3 protrudes outward from the holder 70.

[0102] In this embodiment, a cutting tool 100 used for so-called turning operations is illustrated. Examples of turning operations include internal diameter machining, external diameter machining, and grooving operations. However, the cutting tool 100 is not limited to those used for turning operations. For example, a coated tool 1 may be used as a cutting tool 100 for milling operations. Examples of cutting tools 100 used for milling operations include milling cutters such as flat milling cutters, face milling cutters, side milling cutters, or groove milling cutters, or end mills such as single-flute end mills, multi-flute end mills, tapered end mills, or ball end mills.

[0103] In one embodiment, [1] the coating tool 1 comprises a substrate 10 and a coating layer 20 located on the substrate 10, wherein the coating layer 20 has a Ta-containing laminated structure 22 in which a plurality of layers containing Ta are laminated and in which maximum and minimum values ​​of the atomic % Ta content ratio alternate in the lamination direction, the Ta-containing laminated structure 22 comprises a plurality of high Ta-content layers 22a each containing the maximum value and a plurality of low Ta-content layers 22b each containing the minimum value, the plurality of high Ta-content layers 22a each comprising a plurality of first high Ta-content layers 22aa and a plurality of second high Ta-content layers 22ab each located between adjacent first high Ta-content layers 22aa in the lamination direction, and when the maximum value of the first high Ta-content layer 22aa is taken as the first Ta maximum value and the maximum value of the second high Ta-content layer 22ab is taken as the second Ta maximum value, the second Ta maximum value may be smaller than the first Ta maximum value.

[0104] [2] In the coating tool 1 described in [1] above, the first Ta maximum value may be greater than the atomic percentage of Ta content in the entire Ta-containing laminated structure 22.

[0105] [3] In the coating tool 1 described in [1] or [2] above, the second Ta maximum value may be smaller than the atomic percentage of Ta content in the entire Ta-containing laminated structure 22.

[0106] [4] In any of the coating tools 1 described in [1] to [3] above, a plurality of second Ta-high-content layers 22ab may be located between adjacent first Ta-high-content layers 22aa in the lamination direction.

[0107] [5] In any of the coating tools 1 described in [1] to [4] above, the plurality of Ta-high-content layers 22a may be configured such that the plurality of first Ta-high-content layers 22aa and the plurality of second Ta-high-content layers 22ab are alternately located in the stacking direction.

[0108] [6] In any of the coating tools 1 described in [1] to [5] above, the Ta-containing laminated structure 22 contains light metal A, and in the elemental distribution in the cross-section of the Ta-containing laminated structure 22, the content ratio of composition X is I X , the above I X I X_max , the above I X The minimum value of I X_mIn , the above I X The average value of I X_ave , the above I X The range is the average value of Ix (I X_ave The value obtained by dividing by ) is δI X (=(I X_max -I X_mIn ) / I X_ave In the case of ) δI A <δI Ta That's fine.

[0109] [7] In the coating tool 1 described in [6] above, at least one of the light metals A may be Al or Ti.

[0110] [8] In the coated tool 1 according to any one of the above [1] to [7], the Ta-containing laminated structure 22 has a first region and a second region located farther from the substrate 10 than the first region, and the content ratio of the composition X in the first region is defined as I X1 , the range of the I X1 divided by the average value (I X1 of the I X1_ave ) is defined as δI X1 , the content ratio of the composition X in the second region is defined as I X2 , the range of the I X2 divided by the average value (I X2 of the I X2_ave ) is defined as δI X2 , δI Ta2 <δI Ta1 may be satisfied.

[0111] Further, in one embodiment, [9] the coated tool 1 includes a substrate 10 and a coating layer 20 located on the substrate 10, the coating layer 20 has a Mo-containing laminated structure 23 in which a plurality of layers containing Mo are laminated, and the maximum value and the minimum value of the Mo content ratio in atomic% alternately appear in the lamination direction, the Mo-containing laminated structure 23 has a plurality of Mo high-content layers 23a each including the maximum value, and a plurality of Mo low-content layers 23b each including the minimum value, the plurality of Mo high-content layers 23a include a plurality of first Mo high-content layers 23aa, and a plurality of second Mo high-content layers 23ab respectively located between the first Mo high-content layers 23aa adjacent to each other in the lamination direction, and when the maximum value of the first Mo high-content layer 23aa is defined as a first Mo maximum value and the maximum value of the second Mo high-content layer 23ab is defined as a second Mo maximum value, the second Mo maximum value may be smaller than the first Mo maximum value.

[0112]

[10] In the coated tool 1 according to the above [9], the first Mo maximum value may be larger than the content ratio of Mo in atomic% in the entire Mo-containing laminated structure 23.

[0113]

[11] In the coating tool 1 described in [9] or

[10] above, the second Mo maximum value may be smaller than the atomic percentage of Mo content in the entire Mo-containing laminated structure 23.

[0114]

[12] In any of the coating tools 1 described in [9] to

[11] above, a plurality of second Mo-high-content layers 23ab may be located between adjacent first Mo-high-content layers 23aa in the lamination direction.

[0115]

[13] In any of the coating tools 1 described in [9] to

[12] above, the plurality of Mo-high-content layers 23a may be configured such that the plurality of first Mo-high-content layers 23aa and the plurality of second Mo-high-content layers 23ab are alternately located in the stacking direction.

[0116]

[14] In any of the coating tools 1 described in [9] to

[13] above, the Mo-containing laminated structure 23 contains Al, and in the elemental distribution in the cross-section of the Mo-containing laminated structure 23, the content ratio of composition Y is I Y , the above I Y I Y_max , the above I Y The minimum value of I Y_mIn , the above I Y The average value of I Y_ave , the above I Y The range of I Y The average value (I Y_ave The value obtained by dividing by ) is δI Y (=(I Y_max -I Y_mIn ) / I Y_ave In the case of ) δI Al <δI Mo That's fine.

[0117]

[15] In the coating tool 1 of

[14] above, the Mo-containing laminated structure 23 contains Cr and δI Cr <δI Mo That's fine.

[0118]

[16] In the coating tool 1 of

[14] or

[15] above, the Mo-containing laminated structure 23 has a first Mo region 23A and a second Mo region 23B located further from the substrate 10 than the first Mo region 23A, and the content ratio of the composition Y in the first Mo region 23A is I Y1 , the above I Y1 The range of I Y1 The average value (I Y1_ave The value obtained by dividing by ) is δI Y1 The content ratio of composition Y in the second Mo region 23B is I Y2 , the above I Y2 The range of I Y2 The average value (I Y2_ave The value obtained by dividing by ) is δI Y2 In that case, δI Mo2 <δI Mo1 That's fine.

[0119]

[17] The cutting tool 100 may include a rod-shaped holder 70 having a pocket 73 at its end, and one of the covering tools 1 described in [1] to

[16] above, located within the pocket 73.

[0120] [Examples] The embodiments of this disclosure will be specifically described below with reference to Figures 13 and 14. However, this disclosure is not limited to the embodiments shown below. Figure 13 is a table showing the manufacturing conditions of the coating layer 20 formed on the substrate 10. Figure 14 is a table showing the results of cutting tests on the coating tool 1 for samples No. 1 to No. 12.

[0121] In an AIP apparatus 1000 as shown in Figure 11, coated tools 1 for samples No. 1 to No. 12 were fabricated by forming a coating layer 20 on a substrate 10 made of WC-based cemented carbide according to the manufacturing conditions shown in Figure 13. Specifically, the coating layer 20 was formed on the surface of the substrate 10 under the conditions of arc current (mA), composition of target 105, distance between target 105 and substrate 10 (mm), magnetic flux density near substrate 10 (mT), rotation speed of sample support 106 (revolutions per minute), steady-state bias voltage (V), and pulsed bias voltage as shown in Figure 13. The distance between target 105 and substrate 10 (mm) fluctuated within the range of values ​​shown in Figure 7 due to the rotation of the sample support 106. Accordingly, the magnetic flux density near substrate 10 (mT) also fluctuated within the range of values ​​shown in Figure 7.

[0122] For the coating tool 1 of sample No. 1, multiple Ta-containing laminated structures 22 and multiple Mo-containing laminated structures 23 were formed on the surface of the substrate 10. Here, the multiple Ta-containing laminated structures 22 and multiple Mo-containing laminated structures 23 were stacked alternately. For the coating tool 1 of sample No. 2, only multiple Mo-containing laminated structures 23 were formed on the surface of the substrate 10. For the coating tool 1 of sample No. 3, only multiple Ta-containing laminated structures 22 were formed on the surface of the substrate 10. For the coating tool 1 of sample No. 4, the arc current was reduced and only multiple Ta-containing laminated structures 22 were formed on the surface of the substrate 10. For the coating tool 1 of sample No. 5, the arc current was reduced and only multiple Mo-containing laminated structures 23 were formed on the surface of the substrate 10. For the coating tool 1 of sample No. 6, the pulse period was lengthened and only multiple Ta-containing laminated structures 22 were formed on the surface of the substrate 10. For the coating tool 1 of sample No. 7, the pulse period was lengthened, and only multiple Mo-containing laminated structures 23 were formed on the surface of the substrate 10. For the coating tool 1 of sample No. 8, the pulse width was lengthened, and only multiple Ta-containing laminated structures 22 were formed on the surface of the substrate 10. For the coating tool 1 of sample No. 9, the pulse width was lengthened, and only multiple Mo-containing laminated structures 23 were formed on the surface of the substrate 10.

[0123] Here, on the surface of the substrate 10, a set of Ta-containing laminated structures 22 and Mo-containing laminated structures 23, only Ta-containing laminated structures 22, only Mo-containing laminated structures 23, a set of Ta-containing single-layer structures and Mo-containing single-layer structures, only Ta-containing laminated structures 22, or only Mo-containing laminated structures 23 was formed for the number of times (repeated stacking) shown in Figure 13. That is, the number of Ta-containing laminated structures 22, the number of Mo-containing laminated structures 23, the number of Ta-containing single-layer structures, and the number of Mo-containing single-layer structures were the same as the number of times (repeated stacking) shown in Figure 7. Furthermore, for the stacking time (minutes) shown in Figure 14, each of the Ta-containing laminated structures 22, Mo-containing laminated structures 23, Ta-containing single-layer structures, and Mo-containing single-layer structures was formed on the surface of the substrate 10.

[0124] The coating tools 1 of samples No. 1 to No. 9 correspond to the embodiments of this disclosure. Specifically, the coating tool 1 of sample No. 1 has any of the configurations of the coating tool 1 described in [1] to

[16] above, the coating tools 1 of samples No. 2, 5, 7 and 9 have any of the configurations of the coating tool 1 described in [9] to

[16] above, and the coating tools 1 of samples No. 3, 4, 6 and 8 have any of the configurations of the coating tool 1 described in [1] to [8] above. The coating tools 1 of samples No. 10 to No. 12 correspond to comparative examples of this disclosure and do not have any of the configurations of the coating tool 1 described in [1] to

[16] above.

[0125] <Cutting Test> Cutting tests were performed on coated tool 1 for samples No. 1 to No. 12. The test conditions for the cutting tests were as follows. Using a carbide grade for milling (model number: PNMU1205ANER-GM) as the base material 10, cutting tests were performed under the following conditions.

[0126] (1) Cutting method: Shoulder milling using a square timber measuring 170mm x 260mm x 110mm. (2) Work material: SCМ440 (3) Cutting speed Vc: Low speed (160 m / min) and high speed (300 m / min) (4) Feed rate per tooth fz: 0.12 mm / t (5) Axial cutting depth ap: 2.0 mm (6) Radial cutting depth ae: 63.0 mm (7) Processing method: dry and wet (8) Evaluation method: Milling was performed on the workpiece under the above conditions, and the end of the life of the coated tool 1 was determined when the wear width of the Vb on the tool relief surface reached 0.1 mm.

[0127] Figure 14 is a table showing the results of the cutting tests on coated tool 1 for samples No. 1 to No. 12.

[0128] As shown in Figure 14, the lifespan of the coated tool 1 for samples No. 1 to No. 9 was longer than that of the coated tool 1 for samples No. 10 to No. 12 in both dry and wet machining conditions, under low-speed machining conditions. Furthermore, the lifespan of the coated tool 1 for samples No. 1 to No. 3 was longer than that of the coated tool 1 for samples No. 10 to No. 12 in both dry and wet machining conditions, under high-speed machining conditions.

[0129] Therefore, according to the coating tool 1 of this embodiment, the lifespan of the tool can be extended.

[0130] The shape of the coating tool 1 shown in Figure 1 is merely an example and does not limit the shape of the coating tool 1 according to this disclosure. The coating tool 1 according to this disclosure may, for example, have a rod-shaped body having a rotating shaft and extending from a first end to a second end, a cutting edge located at the first end of the body, and a groove extending spirally from the cutting edge toward the second end of the body.

[0131] Further effects and modifications can be readily derived by those skilled in the art. Therefore, broader aspects of this disclosure are not limited to the specific details and representative embodiments expressed and described above. Accordingly, various modifications are possible without departing from the spirit or scope of the overall concept of the invention as defined by the appended claims and their equivalents. [Explanation of Symbols]

[0132] 1. Covering Tools 2. Chip body 3. Cutting edge 5 Through hole 10 Base 20 Covering layer 21 Middle Class 22 Ta-containing laminated structure 22a Ta high content layer 22aa 1st Ta high content layer 22ab 2nd Ta high content layer 22b Ta low content layer 22ba 1st Ta low content layer 22bb 2nd Ta low content layer 22A 1st Ta area 22B 2nd Ta area 23 Mo-containing laminated structure 23a Mo high content layer 23aa 1st Mo high content layer 23ab 2nd Mo high content layer 23b Mo low content layer 23ba 1st Mo low content layer 23bb Second Mo low content layer 23A 1st Mo area 23B 2nd Mo area 70 Holder 73 pockets 75 screws 100 cutting tools 101 Vacuum Chamber 102 Gas inlet 103 Cathode electrode 104 Anode electrode 105 Target 106 Sample support stand 107 Tower 108 Heater 109 Gas outlet 110 Bias Power Supply 1000 AIP devices L1, L2....dashed lines

Claims

1. Substrate and, A coating layer located on the substrate, Equipped with, The coating layer has a Mo-containing laminated structure in which multiple layers containing Mo are laminated, and in which maximum and minimum values ​​of the atomic percent Mo content ratio alternate in the lamination direction. The aforementioned Mo-containing laminated structure is Each of the following multiple Mo-high content layers includes the aforementioned maximum value, Each of the following layers has a low Mo content, including the aforementioned minimum value: The aforementioned multiple Mo-high content layers are Multiple first Mo-high content layers, It comprises a plurality of second Mo-high-content layers, each located between adjacent first Mo-high-content layers in the stacking direction, The aforementioned multiple low-Mo content layers are Multiple first Mo low-content layers, It comprises a plurality of second low-Mo layers, each located between adjacent first low-Mo layers in the stacking direction, When the maximum value of the first Mo-high-content layer is defined as the first Mo maximum value, and the maximum value of the second Mo-high-content layer is defined as the second Mo maximum value, if the second Mo maximum value is smaller than the first Mo maximum value, The average thickness of the plurality of high-Mo content layers and the plurality of low-Mo content layers is 3 nm or more and 15 nm or less. Each of the plurality of first Mo-high-content layers and the plurality of second Mo-high-content layers has only one maximum value and does not have a minimum value. Each of the plurality of first low Mo content layers and the plurality of second low Mo content layers has only one minimum value and does not have a maximum value. Each of the plurality of first high Mo-content layers is a layer exhibiting a Mo content ratio of 120% or more of the average value of the Mo content ratio in atomic percent in the Mo-containing laminated structure. Each of the plurality of first low Mo-containing layers is a layer exhibiting a Mo content ratio of 75% or less of the average value of the Mo content ratio in atomic percent in the Mo-containing laminated structure. Each of the plurality of second Mo-high-content layers and the plurality of second Mo-low-content layers is a layer exhibiting a Mo content ratio of 75 to 120% of the average value of the Mo content ratio in atomic percent in the Mo-containing laminated structure. The aforementioned Mo-containing laminated structure contains Al, In the elemental distribution in the cross-section of the Mo-containing laminated structure, if the content ratio of composition Y is IY, the maximum value of IY is IY_max, the minimum value of IY is IY_mIn, the average value of IY is IY_ave, and the range of IY is divided by the average value of IY (IY_ave) to obtain δIY (= (IY_max - IY_mIn) / IY_ave), A coated tool where δI Al < δI Mo.

2. The coating tool according to claim 1, wherein the first Mo maximum value is greater than the atomic percentage of Mo content in the Mo-containing laminated structure.

3. The coating tool according to claim 1, wherein the second Mo maximum value is smaller than the atomic percentage of Mo content in the Mo-containing laminated structure.

4. The coating tool according to claim 1, wherein a plurality of second Mo-high-content layers are located between adjacent first Mo-high-content layers in the stacking direction.

5. The coating tool according to claim 1, wherein the plurality of high-Mo content layers are configured such that the plurality of first high-Mo content layers and the plurality of second high-Mo content layers are alternately located in the stacking direction.

6. The aforementioned Mo-containing laminated structure contains Cr, δI Cr <δI Mo The covering tool according to claim 1.

7. The aforementioned Mo-containing laminated structure is The first Mo region and, It has a second Mo region located further away from the substrate than the first Mo region, let the content ratio of the composition Y in the first Mo region be I Y1 , the range of said I Y1 divided by the average value of I Y1 (I Y1_ave ) be δI Y1 , let the content ratio of the composition Y in the second Mo region be I Y2 , the range of said I Y2 divided by the average value of I Y2 (I Y2_ave ) be δI Y2 , then δI Mo2 <δI Mo1 The covering tool according to claim 1.

8. A rod-shaped holder having a pocket at the end, A covering tool according to any one of claims 1 to 7, located within the aforementioned pocket A cutting tool equipped with the following features.

Citation Information

Patent Citations

  • Hard coating ultrahigh temperature high pressure sintered material

    JP2002003284A

  • Surface-coated tool

    JP2010099769A

  • Arc evaporated me11-ame2azi / mo1-b-csicbbzii multilayer coating

    JP2017526817A

  • Coated cutting tool

    JP2018164974A

  • Insert and cutting tool

    JP2022155406A